PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) DAN JIGSAW TERHADAP HASIL BELAJAR SISWA - Miti Miti; Listiani Listiani; Aidil Adhani (Borneo Journal of Biology Education (BJBE), 2025)
Learning models contribute to students' learning outcomes because the way of interaction and collaboration in the learning process can affect the understanding of the material. To determine the effect of cooperative learning models on learning outcomes, a quasi-experimental study with a pretest-posttest nonrandomized control group design was conducted. In this study, Think Pair Share (TPS) and Jigsaw learning models were chosen for learning environmental changes. This research was conducted at MAN Tarakan in November 2024. The research sample was class X.6 students as experiment 1 class and class X.4 students as experiment 2 class. The research instrument used was a test instrument in the form of multiple-choice questions. The results indicated that the posttest scores of students who learned with the Think Pair Share (TPS) learning model were higher than those of students who were taught with the Jigsaw learning model. Hypothesis testing using an independent t-sample t-test was carried out with a confidence level of 95% and obtained a sig (2-tailed) value of 0.441> 0.05, which means that H0 is accepted and H1 is rejected. Based on the hypothesis test, it can be concluded that there was no difference in biology learning outcomes between students who used the TPS learning model and the Jigsaw model. However, the N-gain test results indicated that the TPS model got a value of 61.31%, which was included in the "Quite Effective" category in improving student learning outcomes. In contrast, the Jigsaw model got a value of 54.55%, which is included in the "Less Effective" category. Therefore, it is concluded that although there was no significant difference, the TPS model was more effective than the Jigsaw model in improving learning outcomes.